Evidence for deuteric magnetization in hydrothermally altered Mesozoic basaltic rocks from East Antarctica (Dataset) ... - Løvlie, Reidar (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Evidence for deuteric magnetization in hydrothermally altered Mesozoic basaltic rocks from East Antarctica ...